Identification of Differential-Expressed Genes in Banana-Biostimulant Interaction Using Suppression Subtractive Hybridization - Tatiana Chavez-Navarrete; Luis Sanchez-Timm; Ricardo Pacheco-Coello; Niranjan Baisakh; Efrén Santos-Ordóñez (Agronomy, 2023)
The use of environmental-friendly agricultural inputs to increase yield in crops could reduce environmental contamination and alleviate (a)biotic stress. In this study, we applied a foliar liquid biostimulant to banana plants, which was developed from the anaerobic fermentation of microorganisms with organic remains (manure and plant waste) and minerals to use as environmental-friendly product. To determine the effect of this biostimulant in the plants, a Suppression Subtractive Hybridization (SSH) library was developed from banana leaves in greenhouse conditions. Furthermore, salicylic and jasmonic pathways activation was evaluated by gene expression analysis. First, the application of the biostimulant to banana leaves increased the membrane stability index (MSI), which is directly related to a higher CO2 exchange and assimilation rate. Additionally, the total chlorophyll content increased in plants in comparison with the control plants. In addition, the SSH analysis revealed around 300 expressed sequence tags (ESTs). Several induced genes associated with different molecular pathways, including photosynthesis, anthocyanins production, and plant defense, among others, were encountered after bioinformatic analysis. Upregulated gene expression was demonstrated in different time points, after biostimulant application. Furthermore, induced expression of genes related to the jasmonic acid pathway was observed, which may prove beneficial to the plant under stress conditions.